Once upon a time there was a handsome man. : The virtue of a saint traveling across south-eastern Europe - Barutcieff, Silvia Marin (CEM – Cultura, Espaço & Memória, 2022)
The present paper aims to investigate the function of the dog-headed image of Saint Christopher among the Romanian Orthodox representations of the 18th century. The research will address the relationship between the existing zoomorphic representations and a new hagiography created by the popular lore, which circulated in Wallachia after 1700. This legend converted the monstrous ugliness of the hagiographic hero into his voluntary relinquishment of physical beauty, a semantic change intended to stress Saint Christopher’s virtue. The article will focus on the role of this unusual visual representation within the religious edifice, as well as on the saint’s exemplarity which operates in triggering the contemplation of Christian virtues.